Enhancing Team Performance Unveiling Novel Insights into Teamwork Dynamics - Van-Nghia Nguyen; Nguyen-Quynh-Nhu Ngo; Minh-Thao Truong; Minh-Tung Tran; Thi -Kim-Tuyen Ta (Kurdish Studies, 2024)
This article presents experimental results aimed at assessing the influencing factors on teamwork effectiveness by elucidating the interplay of variables and their impact on collaborative outcomes. The study involved 252 primary data points from students in universities across major provinces and cities in Vietnam. The findings reveal that five factors directly influence students' teamwork effectiveness: the quality of communication within the group, the strength of the team, the goals of group activities, the utilization of resources, and innovation. Moreover, three factors impact teamwork effectiveness through intermediary conditions: knowledge sharing, charismatic leadership, and the skills of team members. These results provide valuable insights for educators and administrators in higher education institutions, offering guidance for enhancing teamwork effectiveness among students.